Sistem Informasi Penilaian Kinerja Pegawai Berbasis Web Di Polda Jambi - Apriyanti, Heny; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2023)
Performance appraisal of employees or State Civil Apparatus at the Jambi Regional Police, is a periodic assessment of the implementation of the work of a State Civil Apparatus. The data processing of the recapitulation of the results of the performance assessment carried out by the Head of the Personnel Division has used a computerized system, namely the Microsoft Office Excel program, which still has weaknesses because it has not been stored in the database, sometimes the results of the performance assessment do not match the reality. The placement of documents is not well organized, so when there is an inspection from the authorities it is difficult to find it. Based on the existing problems, the authors propose the design of a Web-based Employee Performance Assessment Information System that can help the leadership or head of the data processing department, carry out the performance appraisal process properly so as to speed up time and minimize error rates when inputting data. The author performs objectoriented design using use case diagrams, activity diagrams, class diagrams, display designs, database structure tables. The results of this study are a prototype of the Web-based Employee Performance Assessment Information System at the Jambi Regional Police.